2007
DOI: 10.1108/03090560710821288
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentric beliefs and country‐of‐origin (COO) effect

Abstract: Purpose-The present study using the Consumer Ethnocentric Tendencies Scale (CET-SCALE) aims to evaluate the level of consumer ethnocentrism (CE) and its implications on their evaluation of food products. Furthermore, it seeks to examine the level at which country of origin (COO) effect is activated (country, product or attribute) per consumer cluster of different level of CE in a food evaluation context. Design/methodology/approach-For attaining the above aims, a questionnaire was developed and completed by 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(106 citation statements)
references
References 43 publications
5
73
1
Order By: Relevance
“…H5: GSJ and FSJ are associated with the denial of anthropogenic climate change (Feygina et al, 2010;Vainio & Paloniemi, 2013). H6: FSJ is associated with a decreased likelihood of making climate-friendly food choices (Balabanis et al, 2002;Chryssochoidis et al, 2007;Herche, 1992). H7: The denial of anthropogenic climate change is associated with a decreased likelihood of making climate-friendly food choices (Feygina et al, 2010;Vainio & Paloniemi, 2013).…”
Section: Studymentioning
confidence: 99%
“…H5: GSJ and FSJ are associated with the denial of anthropogenic climate change (Feygina et al, 2010;Vainio & Paloniemi, 2013). H6: FSJ is associated with a decreased likelihood of making climate-friendly food choices (Balabanis et al, 2002;Chryssochoidis et al, 2007;Herche, 1992). H7: The denial of anthropogenic climate change is associated with a decreased likelihood of making climate-friendly food choices (Feygina et al, 2010;Vainio & Paloniemi, 2013).…”
Section: Studymentioning
confidence: 99%
“…In studies in which the scales were found to be two-dimensional, factors were labeled as follows: soft and hard consumer ethnocentrism (Chryssochoidis, Krystallis, & Perreas, 2007), domestic availability and core consumer ethnocentrism (Douglas & Nijssen, 2003), emotional and rational ethnocentrism (Acharya & Elliott, 2003), self-reliance and protectionism (Hsu & Nien, 2008), and conservative patriotism and defensive patriotism (Hsu & Nien, 2008). In studies that demonstrated three dimensions, factors were labeled patriotism, protectionism, and socioeconomic conservatism (Marcoux, Filiatrault, & Chéron, 1997) and domestic favouritism, foreign discrimination, and political protectionism (Jakubanecs, Supphellen, & Thorbjørnsen, 2005).…”
Section: Dimensionality Of the Consumer Ethnocentric Tendencies Scalementioning
confidence: 99%
“…Based on the review of literature, there are a few researches which include world-mindedness in purchased decision. The occurrence of time lag is due to the pre and post examinations that were conducted before 2009 often discussed nationalism/patriotism through ethnocentrism study by using CETSCALE measurement (Chryssochoidis et al, 2007). Furthermore, there was no measurement tool that was able to reflect or construct world-mindedness (Riefer & Diamantopoulus, 2009).…”
Section: Sunardi 2009mentioning
confidence: 99%